Antibacterial Activity Test of Srikaya Leaf Ethanol Extract (Annona Squamosa L) Against Staphylococcus Epidermidis with Typical Layer Chromatography Profile - Dian Kurnia Sari; Hari Untarto Swandono (Saniya Institute, 2023)
Srikaya leaves have long been used in traditional medicine for the treatment of cough, fever, rheumatism, diarrhea, and dysentery, as well as an antibacterial and dysentery. The aim of this study is to determine the phytochemical and antibacterial compounds of Srikaya leaf ethanol extract, as well as its antibacterial against Staphylococcus epidermidis bacteria. They also determined the concentration of Srikaya leaf ethanol extract that was most effective in stopping the growth of Staphylococcus epidermidis bacteria. After the Srikaya leaf extract is extracted through the maceration process, phytochemical screening is carried out before the dilution of the extract, which produces 25%, 50% and 75% ethanol concentrations. Disc diffusion method is used to enhance the antibacterial properties of Srikaya leaves on the media Mueller Hinton Agar (MHA). There are alkaloid compounds, flavonoids, tannins, and saponins, according to the findings of this study. With an optimal barrier zone at a concentration of 75% of 11.26 mm, Srikaya leaf extract shows antibacterial capabilities of Staphylococcus epidermidis. It suggests that Srikaya leaf extract contains alkaloids, flavonoids, tannins, and saponins. Further research is needed to find out the antibacterial properties of Srikaya leaves against bacteria such as Bacillus anthraces, Pseudomonas aeruginosa